Carbon-coated pure-phase ferric sodium pyrophosphate as well as preparation method and application thereof

By regulating the reaction conditions and introducing carbon cladding during the preparation process of sodium ferric pyrophosphate material, the problems of phosphate and pyrophosphate are solved, the specific capacity and rate performance of the material are improved, and high conductivity is achieved Preparation of carbon-coated pure phase sodium ferric pyrophosphate.

CN119263248APending Publication Date: 2025-01-07SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411414551.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing iron phosphate phosphate and pyrophosphate have problems in the preparation process, resulting in the electrochemically active sodium phosphate alone, which reduces the specific capacity and rate performance of the material.

Method used

By regulating the reaction conditions during the precursor preparation stage, iron ions, pyrophosphate and phosphate are precipitated simultaneously, pyrophosphate is introduced in advance, combining organic and inorganic carbon sources to form a highly conductive carbon cladding layer, and low-temperature annealing and high-temperature Annealing treatment to obtain carbon-coated pure phase sodium ferric pyrophosphate.

Benefits of technology

The specific capacity and rate performance of the material are improved, and the formation of sodium iron phosphate heterophase without electrochemical activity is avoided, which is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263248A_ABST
    Figure CN119263248A_ABST
Patent Text Reader

Abstract

The invention discloses carbon-coated pure-phase ferric sodium pyrophosphate as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a precipitator with an iron ion-containing solution, and carrying out precipitation reaction to prepare a first precursor; wherein the precipitant comprises phosphate radicals and pyrophosphate radicals; mixing the first precursor with a sodium source, and performing low-temperature annealing treatment to obtain a second precursor; mixing the second precursor with a carbon source, and performing spray drying treatment to obtain a third precursor; wherein the carbon source comprises an organic carbon source and an inorganic carbon source; and carrying out high-temperature annealing treatment on the third precursor to prepare the carbon-coated pure-phase ferric sodium pyrophosphate. According to the carbon-coated pure-phase ferric sodium pyrophosphate prepared by the method, the situation that a ferric sodium phosphate impure phase without electrochemical activity is independently formed in a traditional method is avoided, the specific capacity of the material is improved, and meanwhile, the specific capacity and the rate capability of the NFPP are improved by selecting a proper organic carbon source and a proper inorganic carbon source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a carbon-coated pure-phase phosphate sodium iron pyrophosphate and a preparation method and application thereof. Background Art

[0002] Sodium iron pyrophosphate (NFPP) is a positive electrode material for sodium ion batteries with the advantages of excellent cycle performance, low raw material cost and low processing cost. Its industrial synthesis method is similar to that of lithium iron phosphate. First, the sodium source, phosphorus source, iron source and carbon source are mixed into a slurry, and then the solid particle size in the slurry is reduced by sand grinding and then sprayed to form a precursor, and then the precursor is sintered to obtain the desired material. Therefore, it can be produced using the existing lithium iron phosphate production line, and has good industrialization prospects. However, the structure of sodium iron pyrophosphate prepared by the current method contains both phosphate and pyrophosphate. It is easy for electrochemically inactive sodium iron phosphate to form a single phase during the synthesis, resulting in a reduction in actual capacity, and low-temperature sintering leads to poor conductivity of the carbon coating layer, reducing rate performance and other problems. Summary of the invention

[0003] The main purpose of the present invention is to provide a carbon-coated pure phase phosphate sodium iron pyrophosphate and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0005] The embodiment of the present invention provides a method for preparing carbon-coated pure phase phosphate sodium iron pyrophosphate, which comprises:

[0006] Mixing a precipitant with an iron ion-containing solution and performing a precipitation reaction to obtain a first precursor; wherein the precipitant comprises phosphate and pyrophosphate;

[0007] The first precursor is mixed with a sodium source and subjected to low temperature annealing treatment to obtain a second precursor;

[0008] The second precursor is mixed with a carbon source and subjected to spray drying to obtain a third precursor; wherein the carbon source includes an organic carbon source and an inorganic carbon source;

[0009] And, the third precursor is subjected to high temperature annealing treatment to obtain carbon-coated pure phase phosphate sodium iron pyrophosphate.

[0010] The embodiment of the present invention also provides carbon-coated pure phase phosphate sodium iron pyrophosphate prepared by the aforementioned preparation method.

[0011] The embodiment of the present invention also provides the use of the above-mentioned carbon-coated pure phase phosphate sodium iron pyrophosphate in the preparation of a sodium ion battery positive electrode material or a sodium ion battery.

[0012] An embodiment of the present invention further provides a sodium ion battery positive electrode material, which at least includes the aforementioned carbon-coated pure phase sodium iron phosphate pyrophosphate.

[0013] An embodiment of the present invention further provides a sodium ion battery, which at least includes the aforementioned carbon-coated pure phase sodium iron phosphate pyrophosphate or sodium ion battery positive electrode material.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method provided by the present invention simultaneously precipitates iron ions, pyrophosphate and phosphate by regulating the reaction conditions in the precursor preparation stage to achieve ionic mixing, introduces pyrophosphate into the crystal structure in advance, and increases the energy barrier for phosphate to combine with iron and sodium in the crystal to form a separate phase, thereby avoiding the traditional method of forming an electrochemically inactive sodium iron phosphate impurity phase alone, thereby increasing the specific capacity of the material, and at the same time selecting suitable organic carbon sources and inorganic carbon sources to construct a highly conductive carbon coating layer, thereby improving the specific capacity and rate performance of NFPP. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1a-1b are Raman images of materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0017] Figure 2a-2b is the XRD diagram of the materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0018] Figure 3 It is a schematic diagram of the preparation process of carbon-coated pure phase phosphate sodium iron pyrophosphate in a typical embodiment of the present invention. DETAILED DESCRIPTION

[0019] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Specifically, as one aspect of the technical solution of the present invention, a method for preparing carbon-coated pure phase phosphate sodium iron pyrophosphate involves:

[0021] Mixing a precipitant with an iron ion-containing solution and performing a precipitation reaction to obtain a first precursor; wherein the precipitant contains phosphate and pyrophosphate;

[0022] The first precursor is mixed with a sodium source and subjected to low temperature annealing treatment to obtain a second precursor;

[0023] The second precursor is mixed with a carbon source and subjected to spray drying to obtain a third precursor; wherein the carbon source includes an organic carbon source and an inorganic carbon source;

[0024] And, the third precursor is subjected to high temperature annealing treatment to obtain carbon-coated pure phase phosphate sodium iron pyrophosphate.

[0025] The schematic diagram of the preparation process of the carbon-coated pure phase phosphate sodium iron pyrophosphate in the present invention is as follows Figure 3 shown.

[0026] In some preferred embodiments, the preparation method specifically comprises:

[0027] The precipitant is added dropwise to the iron ion solution and a precipitation reaction is carried out at 40-100° C. to obtain a first precursor; the chemical formula of the first precursor is Fe x H 10-3x P 4 O 15 ·2H 2 O, where x is 2.85-3.15.

[0028] Further, the precipitant includes a pyrophosphate compound, a phosphoric acid compound and a pH adjuster; wherein the pyrophosphate compound includes any one or more combinations of pyrophosphate, sodium pyrophosphate and potassium pyrophosphate; the phosphoric acid compound includes any one or more combinations of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and trisodium phosphate; the pH adjuster includes any one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, citric acid, oxalic acid, ammonium oxalate, ammonia water and sodium hydroxide, and is not limited thereto.

[0029] Furthermore, the pH value of the precipitant is 0.5-6.5.

[0030] Furthermore, the pH value of the precipitant is 1-2.

[0031] Furthermore, the iron ion solution includes an iron salt and an acidulant; wherein the iron salt includes any one or more combinations of ferric sulfate, ferric chloride, and ferric nitrate; the acidulant includes any one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, citric acid, and oxalic acid, and is not limited thereto.

[0032] Furthermore, the concentration of iron ions in the iron ion-containing solution is 0.1-2 mol / L.

[0033] Furthermore, the pH value of the iron ion-containing solution is 0.5-1.5.

[0034] Furthermore, the pH value of the iron ion-containing solution is 0.65-0.95.

[0035] Furthermore, the temperature of the precipitation reaction is 60-85°C.

[0036] Furthermore, x in the chemical formula of the first precursor is 2.9-3.0.

[0037] Furthermore, the molar ratio of the pyrophosphate compound to the phosphate compound in the precipitant is 1:1.9 to 1:2.1.

[0038] In some preferred embodiments, the sodium source includes any one or more combinations of sodium carbonate, sodium hydroxide, sodium oxalate, and sodium nitrate, but is not limited thereto.

[0039] In some preferred embodiments, the molar ratio of the sodium element in the sodium source to the first precursor is 3.8-4.2:1.

[0040] In some preferred embodiments, the temperature of the low temperature annealing treatment is 200-300°C.

[0041] In some preferred embodiments, the low temperature annealing treatment is performed for 2-6 hours.

[0042] In some preferred embodiments, the molar ratio of the second precursor to the carbon atoms in the carbon source is 1:10 to 1:15.

[0043] In some preferred embodiments, the organic carbon source includes any one or more combinations of sucrose, citric acid, glucose, oxalic acid, polyethylene glycol, and polyaniline, but is not limited thereto.

[0044] In some preferred embodiments, the inorganic carbon source includes any one or more combinations of graphene oxide, graphene, carbon nanotubes, conductive carbon black, and octylene, but is not limited thereto.

[0045] In some preferred embodiments, the molar ratio of carbon elements in the organic carbon source to carbon elements in the inorganic carbon source in the carbon source is 100-120:1.

[0046] In some preferred embodiments, the preparation method specifically comprises:

[0047] In a nitrogen or argon-hydrogen mixed gas atmosphere, the third precursor is subjected to a high temperature annealing treatment at 450-550° C. for 8-12 hours to obtain a carbon-coated pure phase sodium iron phosphate pyrophosphate; the chemical formula of the pure phase sodium iron phosphate pyrophosphate in the carbon-coated pure phase sodium iron phosphate pyrophosphate is Na y Fe x P 4 O 15 , where x is 2.85-3.15 and y is 3.8-4.2.

[0048] Furthermore, the x in the chemical formula of the pure phase sodium ferric phosphate pyrophosphate in the carbon-coated pure phase sodium ferric phosphate pyrophosphate is 2.9-3.0.

[0049] In some preferred embodiments, the method for preparing the carbon-coated pure phase phosphate sodium iron pyrophosphate comprises the following steps:

[0050] S1. Preparation of the first precursor: The purpose of this step is to evenly mix iron ions, phosphate and pyrophosphate at the ion level: prepare an iron ion solution as a base liquid, and simultaneously prepare a precipitant containing phosphate and pyrophosphate, and drop the precipitant into the base liquid at a certain rate to precipitate, so as to obtain a first precursor; the base liquid includes an iron salt and an acidulant, the iron salt is one or more of ferric sulfate, ferric chloride and ferric nitrate, the acidulant is one or more of hydrochloric acid, sulfuric acid, nitric acid, citric acid and oxalic acid, the molar concentration of iron ions in the base liquid is 0.1-2 mol / L, the pH value is between 0.5-1.5, and preferably, the pH value is between 0.65-0.95. The above-mentioned precipitant includes a pyrophosphate compound, a phosphoric acid compound and a pH regulator, wherein the pyrophosphate compound includes one or more of pyrophosphate, sodium pyrophosphate and potassium pyrophosphate, the phosphoric acid compound includes one or more of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and trisodium phosphate, the pH regulator includes one or more of hydrochloric acid, sulfuric acid, nitric acid, citric acid, oxalic acid, ammonium oxalate, ammonia water and sodium hydroxide, the molar ratio of the pyrophosphate compound to the phosphoric acid compound in the precipitant is 1:2, the pH value of the precipitant is between 0.5-6.5, preferably, the pH value is between 1-2. The precipitation reaction temperature is 40-100°C, preferably, the reaction temperature is 60-85°C. The first precursor chemical formula is Fe x H 10-3x P 4 O 15 ·2H 2 O, wherein x = 2.85-3.15, preferably, x = 2.9-3.0. The inventors of this case have found through experiments that the first precursor obtained under the preferred reaction conditions is more likely to induce NFPP to transform into a mixed pure phase in the subsequent reaction, reduce the generation of impurities, and obtain a product with better performance.

[0051] S2. Preparation of the second precursor: The purpose of this step is to introduce sodium ions into the system to form a stable precursor core to prevent sodium ions from being excessively dissolved in the slurry during subsequent carbon coating, resulting in carbon source agglomeration and loss of coating effect: the first precursor is mixed with a sodium source, and annealed at a relatively low temperature to obtain a second precursor; wherein the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium oxalate and sodium nitrate, the molar ratio of sodium element in the sodium source to the first precursor is 3.8-4.2:1, the low-temperature annealing temperature is 200-300°C, and the insulation time is 2-6 hours.

[0052] S3, preparation of the third precursor, the purpose of this step is to evenly mix the appropriate inorganic carbon source and organic carbon source and fix them on the surface of the second precursor: add the second precursor to the coating liquid containing the organic carbon source and the inorganic carbon source to mix into a uniform slurry, and spray dry to obtain the third precursor. The organic carbon source includes one or more of sucrose, citric acid, glucose, oxalic acid, polyethylene glycol, and polyaniline, and the inorganic carbon source includes one or more of graphene oxide, carbon nanotubes, conductive carbon black, and footballene. The ratio between the carbon element of the organic carbon source and the carbon element of the inorganic carbon source is 100-120:1.

[0053] S4, finished product sintering: The purpose of this step is to sinter the precursor core into sodium iron phosphate pyrophosphate and form a highly conductive carbon coating on the surface: the third precursor is annealed at a higher temperature to obtain carbon-coated sodium iron phosphate pyrophosphate; the high temperature annealing temperature is 450-550℃, the insulation time is 8-12h, and the atmosphere is nitrogen or argon hydrogen mixed gas. The chemical formula of the obtained product is Na y Fe x P 4 O 15 , wherein x=2.85-3.15, preferably, x=2.9-3.0, wherein y=3.8-4.2.

[0054] Another aspect of the embodiments of the present invention further provides carbon-coated pure phase phosphate sodium iron pyrophosphate prepared by the aforementioned preparation method.

[0055] Another aspect of the embodiments of the present invention further provides the use of the aforementioned carbon-coated pure phase phosphate sodium iron pyrophosphate in the preparation of a sodium ion battery positive electrode material or a sodium ion battery.

[0056] Another aspect of an embodiment of the present invention further provides a sodium ion battery positive electrode material, which at least includes the aforementioned carbon-coated pure phase sodium iron phosphate pyrophosphate.

[0057] Another aspect of an embodiment of the present invention further provides a sodium ion battery, which at least includes the aforementioned carbon-coated pure phase sodium iron phosphate pyrophosphate or sodium ion battery positive electrode material.

[0058] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0059] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0060] Example 1

[0061] S1. Dissolve ferric chloride in pure water to prepare 3L Fe 3+ The base solution with a concentration of 0.1 mol / L was added with hydrochloric acid to adjust the pH value of the base solution to 0.8. Sodium pyrophosphate and diammonium phosphate were dissolved in water to prepare a precipitant with a 4LP element concentration of 0.1 mol / L, and hydrochloric acid was added to adjust the pH value of the precipitant to 1.5. The base solution was heated to 60°C and the precipitant was added to obtain the first precursor.

[0062] S2. Mix the first precursor with sodium carbonate in a molar ratio of 1:2, and then keep the mixture at 250° C. for 5 hours to obtain a second precursor.

[0063] S3. Add oxalic acid and citric acid into water to dissolve, then add the second precursor and graphene, and stir evenly using a high-speed homogenizer, wherein the molar ratio of oxalic acid, citric acid, graphene and the second precursor is: 1.5:1.5:0.1:1, and spray-dry the uniform slurry to form a third precursor.

[0064] S4. Finally, the third precursor is kept at 500° C. for 10 h in a nitrogen atmosphere to obtain a finished product.

[0065] Example 2

[0066] The other processes are the same as those in Example 1, except that the graphene in S3 is replaced by carbon nanotubes.

[0067] Example 3

[0068] The other processes are the same as those in Example 1, except that the pH value of the base solution in S1 is adjusted to 1.5, the pH value of the precipitant is adjusted to 0.5, and the ratio of the first precursor to sodium carbonate in S2 is adjusted to 1:2.12.

[0069] Example 4

[0070] The other processes are the same as those in Example 1, except that the pH of the base solution in S1 is adjusted to 0.5, the pH of the precipitant is adjusted to 6.5, and the ratio of the first precursor to sodium carbonate in S2 is adjusted to 1:1.92.

[0071] Example 5

[0072] The other processes are the same as those in Example 1, except that the pH value of the base solution in S1 is adjusted to 0.65, and the pH value of the precipitant is adjusted to 2.

[0073] Example 6

[0074] The other processes are the same as those in Example 1, except that the pH value of the base solution in S1 is adjusted to 0.95, and the pH value of the precipitant is adjusted to 1.

[0075] Example 7

[0076] S1. Dissolve ferric nitrate in pure water to prepare 3L Fe 3+ Hydrochloric acid was added to the 1 mol / L base solution to adjust the pH value of the base solution to 1.5. Potassium pyrophosphate and disodium hydrogen phosphate were dissolved in water to prepare 4L of a precipitant with a P element concentration of 0.1 mol / L, and citric acid was added to adjust the pH value of the precipitant to 1.5. The base solution was heated to 40°C and the precipitant was added to obtain the first precursor.

[0077] S2. Mix the first precursor with sodium carbonate in a molar ratio of 1:2, and then keep the mixture at 200° C. for 6 hours to obtain a second precursor.

[0078] S3. Add sucrose and glucose into water to dissolve, then add the second precursor and conductive carbon black, and stir evenly using a high-speed homogenizer, wherein the molar ratio of sucrose, glucose, conductive carbon black and the second precursor is 0.8:0.8:0.1:1, and spray-dry the uniform slurry to form a third precursor.

[0079] S4. Finally, the third precursor is kept at 450° C. for 12 h under a nitrogen atmosphere to obtain a finished product.

[0080] Through testing, the finished product showed the same excellent performance in the battery.

[0081] Example 8

[0082] S1. Dissolve ferric sulfate in pure water to prepare 3L Fe 3+ The base liquid with a concentration of 2 mol / L was dripped with hydrochloric acid to adjust the pH value of the base liquid to 1.0. Pyrophosphoric acid and trisodium phosphate were dissolved in water to prepare 4L of precipitant with a P element concentration of 0.1 mol / L, and sodium hydroxide was dripped to adjust the pH value of the precipitant to 3.0. The base liquid was heated to 100°C and the precipitant was dripped to obtain the first precursor.

[0083] S2. Mix the first precursor and sodium oxalate in a molar ratio of 1:2, and then keep the mixture at 300° C. for 2 hours to obtain a second precursor.

[0084] S3. Add polyethylene glycol into water to dissolve it, then add the second precursor and ethylene glycol, and stir evenly using a high-speed homogenizer. The molar ratio of polyethylene glycol (calculated as monomer), ethylene glycol and the second precursor is 5:0.1:1. Spray dry the uniform slurry to form a third precursor.

[0085] S4. Finally, the third precursor is kept at 550° C. for 8 h in a nitrogen atmosphere to obtain a finished product.

[0086] Through testing, the finished product showed the same excellent performance in the battery.

[0087] Comparative Example 1

[0088] Ferrous oxalate, sodium dihydrogen phosphate, citric acid and oxalic acid were prepared into slurry in a molar ratio of 3:4:0.5:2, and the slurry was formed into a precursor through sand milling and spray drying. The precursor was then kept at 500° C. for 10 hours under nitrogen to obtain a finished product.

[0089] Figure 1a-1b The Raman curves of Example 1 and Comparative Example 1 show that the D peak is at 1350 cm -1 Nearby, characterizing the defects of carbon materials, the G peak is at 1580cm -1 The graphitization degree of the carbon material is characterized by the smaller the ratio of the D peak to the G peak, the higher the graphitization degree and the fewer the defects. D / I G Lower, which will lead to better conductivity. Figure 2a-2b is a comparison of the XRD curves of Example 1 and Comparative Example 1, Figure 2a It is a full spectrum of 20-60°. Figure 2b It is a detailed image of 31-35°. It can be seen from the full spectrum that the peak shapes of Example 1 and Comparative Example 1 are similar, but the peak intensity of Example 1 is higher, indicating that its crystallinity is better. In the detailed image, both Example 1 and Comparative Example 1 have characteristic peaks of NFPP phase at 32.0°, 33.6°, and 34.1°, corresponding to (601), (610), and (512) crystal planes, but Comparative Example 1 has characteristic signals of sodium iron phosphate phase at 32.5° and 33.0°, corresponding to (220) and (221) crystal planes, indicating that there are more sodium iron phosphate impurity phases in Comparative Example 1.

[0090] Comparative Example 2

[0091] The other processes are the same as those in Example 1, except that the pH value of the base liquid in S1 is adjusted to 2.0.

[0092] Comparative Example 3

[0093] The other processes are the same as those in Example 1, except that the graphene in S3 is removed.

[0094] Comparative Example 4

[0095] The other processes are the same as those in Example 1, except that the pH value of the base liquid in S1 is adjusted to 0.1.

[0096] Comparative Example 5

[0097] The other processes are the same as those in Example 1, except that the pH value of the precipitant is 0.1.

[0098] Comparative Example 6

[0099] The other processes are the same as those in Example 1, except that the pH value of the precipitant is 8.

[0100] Comparative Example 7

[0101] The other processes are the same as those in Example 1, except that: S2 lacks the low-temperature annealing step, and only the first precursor is mixed with sodium carbonate and then dried.

[0102] Comparative Example 8

[0103] The other processes are the same as those in Example 1, except that: there is too much graphene in S3.

[0104] The materials prepared in Examples 1-8 and Comparative Examples 1-8 were tested, and the results of the power-off test and the ICP test (the ratio was calculated with P fixed at 4) are shown in Table 1.

[0105] Table 1

[0106]

[0107] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0108] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing carbon-coated pure phase phosphate sodium iron pyrophosphate, characterized in that: include: Mixing a precipitant with an iron ion-containing solution and performing a precipitation reaction to obtain a first precursor; wherein the precipitating agent comprises phosphate and pyrophosphate; The first precursor is mixed with a sodium source and subjected to low temperature annealing treatment to obtain a second precursor; The second precursor is mixed with a carbon source and subjected to spray drying to obtain a third precursor; wherein the carbon source includes an organic carbon source and an inorganic carbon source; And, the third precursor is subjected to high temperature annealing treatment to obtain carbon-coated pure phase phosphate sodium iron pyrophosphate.

2. The preparation method according to claim 1, characterized in that: Specifically include: The precipitant is added dropwise to the iron ion solution and a precipitation reaction is carried out at 40-100° C. to obtain a first precursor; the chemical formula of the first precursor is Fe x H 10-3x P4O 15 2H2O, where x is 2.85-3.

15.

3. The preparation method according to claim 2, characterized in that: The precipitant includes a pyrophosphate compound, a phosphoric acid compound and a pH regulator; wherein the pyrophosphate compound includes any one or more combinations of pyrophosphate, sodium pyrophosphate and potassium pyrophosphate; the phosphoric acid compound includes any one or more combinations of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and trisodium phosphate; the pH regulator includes any one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, citric acid, oxalic acid, ammonium oxalate, ammonia water and sodium hydroxide; and / or, the pH value of the precipitant is 0.5-6.5; And / or, the iron ion solution comprises an iron salt and an acidulant; wherein the iron salt comprises any one or more combinations of ferric sulfate, ferric chloride, and ferric nitrate; wherein the acidulant comprises any one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, citric acid, and oxalic acid; And / or, the concentration of iron ions in the iron ion-containing solution is 0.1-2 mol / L; And / or, the pH value of the iron ion-containing solution is 0.5-1.5; And / or, the precipitation reaction temperature is 60-85°C; And / or, x in the chemical formula of the first precursor is 2.9-3.

0.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the pyrophosphate compound to the phosphate compound in the precipitant is 1:1.9 to 1:2.1; And / or, the pH value of the precipitant is 1-2; And / or, the pH value of the iron ion-containing solution is 0.65-0.

95.

5. The preparation method according to claim 1, characterized in that: The sodium source includes any one or more combinations of sodium carbonate, sodium hydroxide, sodium oxalate, and sodium nitrate; and / or, the molar ratio of the sodium element in the sodium source to the first precursor is 3.8-4.2:1; And / or, the temperature of the low temperature annealing treatment is 200-300°C; And / or, the low temperature annealing treatment time is 2-6h; and / or, the molar ratio of the second precursor to the carbon atoms in the carbon source is 1:10 to 1:15; And / or, the organic carbon source includes any one or more combinations of sucrose, citric acid, glucose, oxalic acid, polyethylene glycol, and polyaniline; And / or, the inorganic carbon source includes any one or more combinations of graphene oxide, graphene, carbon nanotubes, conductive carbon black, and octylene; And / or, the molar ratio of carbon element of the organic carbon source to carbon element of the inorganic carbon source in the carbon source is 100-120:

1.

6. The preparation method according to claim 1, characterized in that: Specifically include: In a nitrogen or argon-hydrogen mixed gas atmosphere, the third precursor is subjected to a high temperature annealing treatment at 450-550° C. for 8-12 hours to obtain a carbon-coated pure phase sodium iron phosphate pyrophosphate; the chemical formula of the pure phase sodium iron phosphate pyrophosphate in the carbon-coated pure phase sodium iron phosphate pyrophosphate is Na y Fe x P4O 15 , where x is 2.85-3.15 and y is 3.8-4.

2.

7. Carbon-coated pure phase phosphate sodium iron pyrophosphate prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the carbon-coated pure phase phosphate sodium iron pyrophosphate according to claim 7 in the preparation of a sodium ion battery positive electrode material or a sodium ion battery.

9. A sodium ion battery positive electrode material, characterized in that: At least includes the carbon-coated pure phase phosphate sodium iron pyrophosphate as described in claim 7.

10. A sodium ion battery, characterized in that: At least includes the carbon-coated pure phase sodium iron phosphate pyrophosphate as described in claim 7 or the sodium ion battery positive electrode material as described in claim 9.